ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI OPINI GOING CONCERN (Studi Empiris pada Perusahaan Sektor Consumer Cyclicals yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2021) - Nurhana Fajri Herawati; Paulus Theodorus Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2023)
This study aims to analyze and provide empirical evidence of the effect of the previous year's going concern opinion, audit quality, audit lag, company size, profitability, liquidity, and leverage on going concern opinion acceptance. This study has a dependent variable, namely going concern audit opinion with independent variables including previous year's going concern opinion, audit quality, audit lag, company size, profitability, liquidity, and leverage. This study uses secondary data obtained from financial reports and independent auditor reports published on the official website of the Indonesia Stock Exchange www.idx.co.id. The sample of this study is the consumer cyclicals sector companies listed on the Indonesia Stock Exchange in 2018-2021. Sampling using purposive sampling and obtained a sample of 63 companies in this study. Hypothesis testing was carried out using logistic regression. The test results show that there is a significant effect on the previous year's going concern opinion variable, audit quality, and profitability on going concern opinion acceptance. However, audit quality has the opposite direction to the hypothesis formulated, thus making the variable hypothesis rejected. For audit lag variables, company size, liquidity, and leverage have no significant effect on going concern opinion acceptance.